CPWF Annual Report 2006 - CGIAR Challenge Program on Water and Food (CGIAR Challenge Program on Water and Food, 2007)
The CGIAR Challenge Program on Water and Food (CPWF) is a multi-institutional research for development program that seeks to create and disseminate international public goods to improve the productivity of water in river basins in ways that are pro-poor, gender equitable and environmentally sustainable. In doing so, CPWF contributes to efforts by the global community to ensure that global diversions of water to agriculture are maintained at the level of the year 2000. The specific objectives of the Program are to increase food production using less water, to improve livelihoods and nutrition of the rural and peri-urban poor, to decrease water pollution from agriculture, to maintain water-related ecosystems services and to reduce water-related diseases. To address these objectives, the program is structured into five thematic areas: crop water productivity improvement; water and people in catchments; aquatic ecosystems and fisheries; integrated basin water management; and the global and national water and food system. Research is conducted in nine benchmark river basins, including the Andean system, Indus-Ganges, Karkheh, Limpopo, Mekong, Nile, Sao Francisco, Volta and the Yellow. Research in the Challenge Program is implemented through one of four focused research initiatives. First call projects, selected through a competitive process, make up the greater part of the present CPWF research portfolio. Basin focal projects add value to individual research project outputs by identifying in specific benchmark basins opportunities for water-related interventions to achieve CPWF and partner development goals. Small grants for impact serve to remind Program researchers of how their research should have practical outcomes for communities on the ground. Synthesis research is essential to drawing together a large body of disparate and diverse information into a comprehensive whole.